Determinants of Government Membership at the Subnational Level: Empirical Evidence from Large Cities in Germany (1999–2016). Issue 1 (18th January 2023) - Gross, Martin
Abstract: Coalition governments prevail at the European subnational level. Although some studies explain the formation of subnational government coalitions, we know little about the determinants of individual parties' likelihood of joining such coalitions. This article aims to fill this gap in empirical and theoretical ways. It shows that an important institutional constraint matters for political actors' strategies when forming subnational coalitions: the party affiliation of the directly elected head of the executive. Being the party of the head of the executive or being ideologically close to that party significantly increases a party's likelihood of joining a coalition. The empirical evidence results from multinomial choice models using a novel data set on subnational parties' likelihood of joining 92 coalition governments at the local level in Germany between 1999 and 2016. The findings have substantive implications for subnational institutional settings resembling 'mixed' political systems (i.e. neither purely presidential nor purely parliamentarian).